GRAPHICAL REPRESENTATION OF PERIODIC MOTION OF THE LINE OF NODES OF THE MOON - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1993)
In the text-books of astronomy, sections generally related to the Moon deal with the orbital elements of the Earth-Moon system such as a, e, i, OMEGA, omega and the time of perigee passage tau. While the MEAN of the first of the three elements do not vary, mean longitude of the ascending node-mean longitude of the lunar perigee and the time of perigee passage undergoes secular as well as periodic changes due predominantly to the action of the Sun's gravitational attraction. While to a certain degree, explanations related to the calculation of the lunar orbit parameters are given. not a single graphical representation of these short- or long-periodic changes are presented. We allow the number of data related to these periodic changes must cover a large span of time; and if regression of the line of nodes or advances of the line of apses are to be graphically seen, data covering 18.61 and 8.85 yr, respectively, are needed. In this work we particularly aim at the graphical representation of the periodic changes of the line of nodes.